EFFORTS TO IMPROVE THE CAPABILITY OF SCHOOL PRINCIPALS IN IMPLEMENTING ACADEMIC SUPERVISION THROUGH PRODEP PROGRAM REPLICATION ASSISTANCE BY SCHOOL SUPERVISORS IN 5 FOSTER SCHOOLS IN MAKASSAR CITY - Raisuddin, Muhammad (Sains Global Institut, 2019)
School Action Research was conducted with the aim of increasing the ability of principals to carry out academic supervision in five Makassar City target schools in the 2018-2019 academic year. Actions are carried out through screening through replication of the proDEP program. The results of the study concluded that by providing assistance through measures, the ability of principals to carry out academic supervision increased. Indicators of increasing the ability to carry out academic supervision of principals are measured through the completeness, quality and authenticity of their work. from cycle 1 with a value of 80.93 to cycle 2 with a value of 95.93.